2013
DOI: 10.4330/wjc.v5.i6.186
|View full text |Cite
|
Sign up to set email alerts
|

Depression in adults with congenital heart disease-public health challenge in a rapidly expanding new patient population

Abstract: There is a growing population of adults with congenital heart disease (CHD) due to improved survival beyond childhood. It has been suggested that adults with CHD may be at increased risk for mental health problems, particularly depression. The reported incidence of depression in CHD varies from 9% to 30%. This review examines the evidence for a higher depression rate in CHD vs general population. Possible explanations are offered from a variety of disease models, ranging from brain injury to the psychoanalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Depression and anxiety symptoms are commonly seen in over 50% of adolescents and adults with SVHD (Bromberg et al, ; Cohen et al, ). Unfortunately, most SVHD patients go underdiagnosed and undertreated (Pauliks ). In our study, multiple brain areas, including the cingulate, insula, cerebellum, and para‐hippocampal gyrus showed tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety symptoms are commonly seen in over 50% of adolescents and adults with SVHD (Bromberg et al, ; Cohen et al, ). Unfortunately, most SVHD patients go underdiagnosed and undertreated (Pauliks ). In our study, multiple brain areas, including the cingulate, insula, cerebellum, and para‐hippocampal gyrus showed tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…Many abnormalities in complex congenital heart disease such as ventricular dysfunction, pulmonary hypertension, and muscle weakness have contributed to an impairment of physical fitness. Exercise intolerance in ACHD has also led to a poor quality of life . Therefore, improving exercise capacity is important in the care of patients with ACHD.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise intolerance in ACHD has also led to a poor quality of life. 2,3 Therefore, improving exercise capacity is important in the care of patients with ACHD.…”
Section: Introductionmentioning
confidence: 99%